Dynamics and Performance of Livestock and Poultry Sector in India: A Spatio-Temporal Analysis - Mondal, Soumyabrata; Mishra, Anand Prasad (National Geographical Journal of India, 2022)
Livestock have remained an integral part of the socio-economic fabric of rural India since time immemorial as a source of livelihood and a provider of draught energy, manure and fuel. Sustained increase in income and urbanization are now fuelling rapid growth in demand for animal food products, and the livestock are coming under pressure to produce more and more. Over the four decades livestock production grew faster than crop sector as a whole and made signicant contribution to agricultural growth, which is considered to be an important factor in poverty reduction in most developing countries. India's livestock sector is one of the largest in the world with a holding of 11.6% th of world livestock population as per 19 livestock census report. Contribution of livestock to the national economy in terms of Gross Domestic Product (GDP) is 4.11% and it also shares 25.6 % of total agricultural GDP during 2015-16.The livestock sector is an important source of foreign exchange too and is performing well in the manner of production, value addition and export of dairy, shery, wool, poultry and other products. Hence, the present study analyzes the status, performance and growth trend of livestock production and population in India as well as in different states vividly. The entire study is based on secondary sources of data. Tabular analyses, percentage compilation, Compound Annual Growth Rate have been used for easy analysis and comparison. The entire study tells that overall despite the regional disparities in livestock population and production across different states in our country, the production and growth rate in this sector is steadily increasing that enhances overall economic development of our nation